Psychological problems of personality’s lifestyle - Emishyants, Olga (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
This article discusses lifestyle as the basis of the human psyche, which is formed in childhood. Lifestyle ‒ a concept adopted human life, crystallized pattern of behavior that affects all areas of human life, the main purpose of human life and cannot be considered separately. Mental phenomena should be seen as parts of a whole. According to A. Adler, tendency that we see in adults is actually a direct projection of experiencing him in childhood. Communication between experiences, impressions, social attitudes childhood and later mental phenomena seen the example of a client with obsessive-compulsive syndrome.